2019
DOI: 10.5194/hess-23-3081-2019
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal changes in aridity of Pakistan during 1901–2016

Abstract: Abstract. The changing characteristics of aridity over a larger spatiotemporal scale have gained interest in recent years due to climate change. The long-term (1901–2016) changes in spatiotemporal patterns of annual and seasonal aridity during two major crop growing seasons of Pakistan, Kharif and Rabi, are evaluated in this study using gridded precipitation and potential evapotranspiration (PET) data. The UNESCO aridity index was used to estimate aridity at each grid point for all the years between 1901 and 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 61 publications
(80 reference statements)
5
29
0
Order By: Relevance
“…The findings from this present study corroborate the findings of few studies conducted in the nearby countries, such as [34,43,48,76] which showed a generally decreasing trend in the water storage and increasing aridity [81,82] in the Central Asia region. This emphasizes how important it is to conserve and improve water resources management in the region, particularly for Afghanistan where more populace would need the resource for irrigation purposes in the future as the population continues to grow and the climate continues to change.…”
Section: Discussionsupporting
confidence: 90%
“…The findings from this present study corroborate the findings of few studies conducted in the nearby countries, such as [34,43,48,76] which showed a generally decreasing trend in the water storage and increasing aridity [81,82] in the Central Asia region. This emphasizes how important it is to conserve and improve water resources management in the region, particularly for Afghanistan where more populace would need the resource for irrigation purposes in the future as the population continues to grow and the climate continues to change.…”
Section: Discussionsupporting
confidence: 90%
“…MK tests are used widely in the environmental sciences, assisting in measurements and analyses of temperature, precipitation, sunshine hours, cloud cover, relative humidity and wind speed [68]; temperature and precipitation [66]; precipitation [69]; extreme temperatures [42,43,67,70]; hail [71][72][73][74]; aridity [17][18][19]32,75]; evapotranspiration [76]; and atmospheric deposition [77]. MK tests are simple, robust, and can cope with missing values.…”
Section: Discussionmentioning
confidence: 99%
“…There are several trend assessments approaches available in the literature. However, the Mann-Kendall test is the most widely used test for assessing the trends in hydro-climatic studies [18,[52][53][54][55][56]. The Mann-Kendall test [57] which is recommended by the World Meteorological Organization (WMO) often used as because it has several advantages: It does consider the data distribution, and it can cope with the outliers [58][59][60][61].…”
Section: Mann-kendall Trend Testmentioning
confidence: 99%